Potential of selected fungal species to degrade wheat straw, the most abundant plant raw material in Europe - Jasmina Ćilerdžić; Milica Galić; Jelena Vukojević; Ilija Brčeski; Mirjana Stajić (BMC Plant Biology, 2017)
Abstract Background Structural component of plant biomass, lignocellulose, is the most abundant renewable resource in nature. Lignin is the most recalcitrant natural aromatic polymer and its degradation presents great challenge. Nowadays, the special attention is given to biological delignification, the process where white-rot fungi take the crucial place owing to strong ligninolytic enzyme system. However, fungal species, even strains, differ in potential to produce high active ligninolytic enzymes and consequently to delignify plant biomass. Therefore, the goals of the study were characterization of Mn-oxidizing peroxidases and laccases of numerous mushrooms as well as determination of their potential to delignify wheat straw, the plant raw material that, according to annual yield, takes the first place in Europe and the second one in the world. Results During wheat straw fermentation, Lentinus edodes HAI 858 produced the most active Mn-dependent and Mn-independent peroxidases (1443.2 U L−1 and 1045.5 U L−1, respectively), while Pleurotus eryngii HAI 711 was the best laccase producer (7804.3 U L−1). Visualized bends on zymogram confirmed these activities and demonstrated that laccases were the dominant ligninolytic enzymes in the studied species. Ganoderma lucidum BEOFB 435 showed considerable ability to degrade lignin (58.5%) and especially hemicellulose (74.8%), while the cellulose remained almost intact (0.7%). Remarkable selectivity in lignocellulose degradation was also noted in Pleurotus pulmonarius HAI 573 where degraded amounts of lignin, hemicellulose and cellulose were in ratio of 50.4%:15.3%:3.8%. Conclusions According to the presented results, it can be concluded that white-rot fungi, due to ligninolytic enzymes features and degradation potential, could be important participants in various biotechnological processes including biotransformation of lignocellulose residues/wastes in food, feed, paper and biofuels.